Pyrethroid Resistance Situation across Different Eco-Epidemiological Settings in Cameroon - Nelly Armanda Kala-Chouakeu; Paulette Ndjeunia-Mbiakop; Idriss Nasser Ngangue-Siewe; Konstantinos Mavridis; Vasileia Balabanidou; Roland Bamou; Mabu Maxim Bindamu; Abdou Talipouo; Landre Djamouko-Djonkam; Jean Arthur Mbida-Mbida; Jeanette Tombi; John Vontas; et al. (Molecules, 2022)
Rapid emergence and spread of pyrethroid resistance in Anopheles gambiae populations is among the main factors affecting malaria vector control in Cameroon, but there is still not enough data on the exact pyrethroid resistance status across Cameroon. The present study assessed pyrethroid resistance profile in different eco-epidemiological settings in Cameroon. Susceptibility bioassay tests were performed with F0 An. gambiae females aged three to five days. Mosquito susceptibility to both permethrin and deltamethrin was assessed. Species of the An. gambiae s.l. complex were identified using molecular diagnostic tools. Target site mutations conferring resistance were detected using Taqman assays. Quantitative reverse transcription-real-time PCR (qRT-PCR) 3-plex TaqMan® assays were used for the quantification of detoxification genes implicated in pyrethroid resistance. An. gambiae, An. coluzzii and An. arabiensis were identified in the different settings. An. gambiae was dominant in Santchou, Kékem, Bélabo, Bertoua and Njombé, while An. coluzzii was abundant in Tibati and Kaélé. High frequencies of the kdr L1014F allele ranging from 43% to 100% were recorded in almost all sites. The L1014S kdr allele was detected at low frequency (4.10–10%) only in mosquito populations from Njombé and Tibati. The N1575Y mutation was recorded in Kaélé, Santchou, Tibati and Bertoua with a frequency varying from 2.10% to 11.70%. Six Cytochrome P450 genes (Cyp6p3, Cyp6m2, Cyp9k1, Cyp6p4, Cyp6z1, and Cyp4g16) were found to be overexpressed in at least one population. Analysis of cuticular hydrocarbon lipids indicated a significant increase in CHC content in mosquito populations from Kaélé and Njombé compared to Kékem, Bélabo and Bertoua populations. The study indicated high pyrethroid resistance across different ecological settings in Cameroon with different profile of resistance across the country. The present situation calls for further actions in order to mitigate the impact of insecticide resistance on vector control measures.